SKA1/2/3 is a biomarker of poor prognosis in human hepatocellular carcinoma - Song, Guo-Qiang; He, Tian-Li; Ji, Ke-Jie; Duan, Yi-Meng; Zhang, Jia-Wen; Hu, Guo-Qiang (Frontiers in Oncology, 2022)
Background Spindle and kinetochore-associated complex subunits 1–3 (SKA1–3) stabilize the kinetochore-attached spindle microtubules in metaphase. Due to the dysregulation in multiple cancers, SKA1–3 is considered a predictor for the prognosis of the patients. However, the potential clinical applications of SKA1–3, particularly in hepatocellular carcinoma (HCC) prognosis and progression, have completely unknown yet. Methods For the analysis of SKA1–3 expression and applications in clinics in HCC patients, several databases, such as STRING, UALCAN, GEO, and TCGA, were searched. In addition, the underlying mechanisms of SKA for the regulation of HCC occurrence, development, and progression were also explored. Results Compared to the normal controls, HCC patients showed dramatically elevated SKA1–3 expression at the mRNA level, and the values of the area under the curve (AUC) were 0.982, 0.887, and 0.973, respectively. Increased SKA1–3 expression levels were associated with the clinical stage, age, body mass index, tumor grade, tissue subtype, and Tp53 mutation status in HCC patients. The analyses of Kyoto Encyclopedia of Genes and Genome (KEGG) and Gene ontology (GO) demonstrated that SKA1–3 are enriched mainly in the Fanconi anemia, homologous recombination, spliceosome, DNA replication, and cell cycle signaling pathways. The hub genes, such as CDK1, CCNB1, CCNA2, TOP2A, BUB1, AURKB, CCNB2, BUB1B, NCAPG, and KIF11, were identified in protein–protein interactions (PPIs). The expression levels of hub genes were increased in HCC patients and predictive of a poor prognosis. Finally, the expression levels of SKA1–3 were determined using the GEO database. Conclusions SKA1–3 are potential prognostic biomarkers of and targets for HCC. In addition, SKA1–3 may affect HCC prognosis via the Fanconi anemia pathway, homologous recombination, spliceosome, DNA replication, and cell cycle signaling pathway.